MYCORRHIZAL FUNGI INCREASED EARLY GROWTH OF TROPICAL TREE SEEDLINGS IN ADVERSE SOIL - Maman Turjaman; Erdy Santoso; Irnayuli R. Sitepu; Keitaro Tawaraya; Erry Purnomo; Ronny Tambunan; Mitsuru Osaki (Indonesian Journal of Forestry Research, 2009)
The rate of reforestation  has increased throughout the countries in Southeast Asia region during the last 20 years.  At the same time, inconvenient situations such as forest destruction, forest exploitation, illegal logging, clear-cut forest areas, old agricultural lands, post-wildfire areas, conversion  of natural  forests into  plantations, resettlement areas, mine  lands,  and amended adverse soils have also been increasing  significantly. Mycorrhizas, hovewer,  play important role  to increase  plant  growth,  enrich  nutrient content  and enhance  survival rates of forest tree species in temperate  and sub-tropical  regions.  Unfortunately, a little information so far is available  regarding  the effect of mycorrhizas on growth  of tree species growing  in tropical  forests. In relevant,  several experiments  were carried  out to determine whether  ectomycorrhizal (ECM) fungi and arbuscular  mycorrhizal (AM) fungi can enhance mycorrhizal colonization, nutrient content, and plant growth of some tropical rain forest tree species in Indonesia under nursery  and field conditions.   The families of tropical  tree species used in the experiment were  Thymelaeaceae (Aquilaria crassna), Leguminosae  (Sesbania grandifolia), Guttiferae (Ploiarium alternifolium and Calophyllum hosei), Apocynaceae (Dyera polyphylla and Alstonia scholaris), and Dipterocarpaceae (Shorea belangeran). These families are important as they provide timber  and non-timber  forest products (NTFPs).   This paper discusses the role of mycorrhizal fungi in increasing  early  growth  of tropical  tree seedlings in adverse soil.